Health and Safety Management on Construction Projects: The View of Construction Tradespeople - Eze, Emmanuel; Sofolahan, Onyinye; Siunoje, Lawrence (CSID Journal of Infrastructure Development, 2020)
The complex networks of activities of construction projects have made the construction environment unfriendly and unsafe for the construction tradespeople. Tradespeople play a key role in construction project delivery and are the major victims of accidents that affect negatively on project performance. This study assessed the perception of construction tradespeople on the health and safety management on the construction site. The study objectives are; to determine the trade with the highest accident exposure level, to ascertain the types of accidents and level of occurrence, to determine the major causes of accidents on construction sites, and to examine the possible measures for preventing accidents on construction sites. A well-structured questionnaire and stratified purposive sampling technique were adopted in gathering data from the participants in Abuja, Nigeria. With a reliability index of at least 0.80, the gathered data were analysed using frequencies, percentiles, mean analytics, Kruskal-Wallis test, and Mann-Whitney U tests. The study found that Concreters/Mason/Bricklayers, Carpenters, and Steel benders/fixers/welders are the most vulnerable trades groups to hazards and accidents on construction sites. Fall-related, Slip and trip, and contact with objects (struck by objects) are the most occurring accident types. The most critical causes of accidents based on tradespeople perception are; inadequate training, drugs and alcohol, horseplay by workers, excessive working hours resulting in mental fatigue, and communication issues. The most important measures for preventing accidents on construction sites are; rewards and penalties for defaulters, the use of personal protective equipment, effective communication system on-site, correct placement of ladder through proper supervision, and site discipline among workers. The study concludes that there is a low level of implementation of health and safety management practices on construction projects site by construction organisations. Rewards for safety compliances and penalties for HS deviant workers should be put in place by the management of construction sites.